Echinoderms of the biological collection of the Laboratorio de Ecología Molecular, Microbiología y Taxonomía (LEMITAX) of the Universidad de Guadalajara, Mexico - Hueytletl-Pérez, Miriam; Granja-Fernández, Rebeca; Galván-Villa, Cristian Moisés; Rodríguez-Zaragoza, Fabián Alejandro; Ríos-Jara, Eduardo (Revista de Biología Tropical, 2024)
Introduction: The biological collections represent the foundation for the knowledge and management of the biodiversity of a region. However, regional collections focused on echinoderms are scarce in Mexico, particularly in the Central Mexican Pacific (CMP). The biological collection of the Laboratorio de Ecología Molecular, Microbiología y Taxonomía (LEMITAX) belongs to the Centro Universitario de Ciencias Biológicas y Agropecuarias of the Universidad de Guadalajara, Jalisco, Mexico and it aims to serve as a reference for the region’s marine biodiversity. Objective: To state the richness of echinoderms in the LEMITAX collection. Methods: The organisms deposited at the LEMITAX have been collected by SCUBA, free-diving, and bottom trawls with biological dredges in different areas of the Mexican Pacific. The specimens are wet-preserved (70 % ethanol; Asteroidea, Echinoidea, Holothuroidea, and Ophiuroidea) or dried (Asteroidea and Echinoidea). Results: The specimens are from the states of Sinaloa, Nayarit, Jalisco, and Colima, including two natural protected areas (NPAs), the Isabel Island National Park and the sanctuary of the Islands and Islets of Bahía de Chamela. The collection has 20 761 specimens of echinoderms distributed in 75 species (10 asteroids, 17 ophiuroids, 17 echinoids, and 31 holothuroids). The best-represented state is Jalisco (64 species), followed by Nayarit (31), Colima (20), and Sinaloa (11). Concerning the NPAs, Chamela is the best represented (60), followed by Isabel Island (22). Thirty-four new records are added; the largest contribution is for Chamela, with 14 new records, followed by the state of Jalisco (seven), Nayarit (four), Colima (three), and Isabel Island (three). For the CMP, the presence of Astropecten ornatissimus, Luidia phragma, Cucumaria crax, and Holothuria (Cystipus) casoae, is reported for the first time, updating the echinoderm richness to 197 species. The bathymetric distribution range of Ophiactis simplex, Ophiocomella alexandri, and Holothuria (Cystipus) casoae is extended, as well as the geographic range of Cucumaria crax. Conclusions: The biological collections deposited in the universities contribute substantially to the knowledge of biodiversity, as reflected in the LEMITAX collection, whose revision resulted in the updating of the echinoderm richness in the region.